The dual role of vulvovaginal candidiasis in HPV infection: implications for vaginal microecology and cervical lesions - Zhang, Xiaoyuan; Yao, Mengxing; Huang, Yuan; Wang, Huiqin; Li, Hui; Ma, Juanwen (Frontiers in Microbiology, 2026)
Persistent infection with human papillomavirus (HPV) is a major pathogenic factor in the development of cervical lesions and cervical cancer. Its occurrence is not only related to the virus itself but also closely associated with the stability of the host vaginal microecological environment. In particular, microbial dysbiosis caused by vaginal infections such as bacterial vaginosis (BV), trichomoniasis (TV), and vulvovaginal candidiasis (VVC) may facilitate HPV acquisition and persistence. Among these factors, VVC has drawn special attention due to its unique bidirectional role: it may promote persistent HPV infection by inducing local inflammation and disrupting epithelial barrier function, while under certain conditions, it may also activate immune responses that suppress viral activity. This dual nature offers novel mechanistic insights into HPV-related cervical pathogenesis. This review systematically summarizes current evidence on the interplay between persistent HPV infection and vaginal microecological imbalance, with a particular focus on the dual regulatory role of VVC and its potential influence on the expression of the HPV oncogenes E6 and E7 oncogenes. By integrating recent mechanistic findings, the review aims to provide a theoretical foundation and clinical reference for microecology-based interventions to improve HPV-related outcomes and prevent cervical lesions.